Post‐operative survival in head and neck cancer patients with elevated troponins. (30th November 2022) - Hua, Gordon; Levin, Marc; Zhang, Han; Xie, Michael; McHugh, Tobial; Gupta, Michael
Abstract: Objectives: The strenuous demands of head and neck cancer surgery (HNS) place patients at increased risk of myocardial injury. Troponin positivity (TP) post‐operatively is a predictor of increased complications and mortality. The present study is the first to investigate the effects of TP on potential delays in adjuvant treatment and disease‐specific survival. Design, Setting, Participants and Main outcome measures: All patients undergoing HNS from 2014 to 2016 had troponins measured at a single academic centre. Relevant patient data was extracted on retrospective chart review. The main outcome measures were the impact of TP on timing of adjuvant treatment and disease‐specific survival. Results: Of 166 patients, 26 (15.6%) developed TP post‐operatively. There was no significant difference between cohorts for baseline characteristics except for age. Overall and disease‐specific survival for TP patients were respectively 45.9% and 57.4% at 3 years. There was no significant difference between cohorts for overall and disease‐specific survival, and time to adjuvant therapy. Conclusion: No significant association was found between TP and overall and disease‐specific survival, and time to adjuvant therapy.